(3JUajI GdCPgGf hfaGP GdacQ hTMP GdbdhHs - (3GdaVd Hf Sgds; (3cfLhQ Hf GSafOjGQs
(3ChdgG (B:s
(3CeG HYO(B: (3aEf CaVd eGGYWi GdYHO ai GdOfjG GdMceI hai GdBNQI GdQMeI hCaVd eGCYXi GdYHO ai faSg GdehYXI hCaVd eG jfGd GdYHO dfaSg GdYGajI hCaVd eG bGd GdYHO (B:(3dG Edg EdG Gddg s
(3BNQgG (B:s
(3adG jahJfce GdYde hbQGAI GdcJH aEfgG COH hYde bO bjOg dce ef eVi bdHce , dJROGOhG Hg ZbdG hegGQI hageG hHGddg GdJhajb s
(3KdGKhf hQbI abW ef JQLeI LGhjOGf NQOs
(3YdjgG YOI JedcGJ CbOegG SfI (B1108(3g`s
(3hgPG GdcJGH gh CUd cJGH LGhjOGf NQO GdPi RGO Ydjg GHf eSchjg ef BOGH GdYQH hGdQhe hGdgfOs
(3hGfXQ LGhjOGf NQO s
(3JHUQI GdYfhGf (B:s
(3JQLeI(B/(3fbds
Keywords: (3GdCOHs